2012
DOI: 10.1177/0194599811434482
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Outcomes in an Access‐to‐Care Laryngeal Cancer Cohort

Abstract: Objective Human papillomavirus (HPV), particularly HPV16, is a causative agent for 25% of head and neck squamous cell cancer, including laryngeal squamous cell cancer (LSCC). HPV positive (HPV+ve) patients, particularly oropharyngeal SCC, have improved prognosis. For LSCC, this remains to be established. The goal was to determine stage and survival outcomes in LSCC in the context of HPV infection. Study Design Historical cohort study. Setting Primary care academic health system. Subjects and Methods In 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 26 publications
3
59
0
1
Order By: Relevance
“…Importantly, only four studies [8,9,29,88,95] examined the impact of HPV on the outcome of a total of 319 patients; 134 of which were HPVpositive. No association of HPV status with outcome was found.…”
Section: Hpv and Laryngeal Cancermentioning
confidence: 99%
“…Importantly, only four studies [8,9,29,88,95] examined the impact of HPV on the outcome of a total of 319 patients; 134 of which were HPVpositive. No association of HPV status with outcome was found.…”
Section: Hpv and Laryngeal Cancermentioning
confidence: 99%
“…16 The cutoff value for HPV16-positive status was ≥0.03 (≥3 HPV genome copies/100 cells). 16,18,19 Bisulfite Modification and Quantitative Methylation-Specific Polymerase Chain Reaction (QMSP) Assay…”
Section: Hpv16 Detection By Means Of Quantitative Polymerase Chain Rementioning
confidence: 99%
“…In a pooled meta analysis study 7 using conventional PCR based assays, prevalence of HPV16 in LSCC was 17%. 7 In a recent study, HPV16, detected by real-time quantitative PCR, had a reported prevalence of 27%, supporting a role for HPV in LSCC 28 .…”
Section: Discussionmentioning
confidence: 95%
“…Specific primers and probes were designed to amplify a housekeeping gene, β-globin 13 (to standardize the input DNA), and the E6 region of HPV16 14 as previously described. 15 DNA amplifications were carried out in a 96-well reaction plate format in an Applied Biosystems 7900HT Sequence Detector (Applied Biosystems, Foster City, CA). Multiple water blanks were included in every run.…”
Section: Hpv16 Detection By Quantitative Pcr (Qpcr)mentioning
confidence: 99%